Sewage sludge, compost and other representative organic wastes as agricultural soil amendments: benefits versus limiting factors - Alvarenga, Paula (2015)
Nine different samples of sewage sludges, composts and other representative organic wastes, with potential interest to be used as agricultural soil amendments, were characterized: municipal sewage sludge (SS1 and SS2), agro industrial sludge (AIS), municipal slaughterhouse sludge (MSS), mixed municipal solid waste compost (MMSWC), agricultural wastes compost (AWC), compost produced from agricultural wastes and sewage sludge (AWSSC), pig slurry digestate (PSD) and paper mill wastes (PMW). The characterization was made considering their: (i) physicochemical parameters, (ii) total and bioavailable heavy metals (Cd, Cr, Cu, Ni, Pb, Zn and Hg), (iii) organic contaminants, (iv) pathogenic microorganisms and (v) stability and phytotoxicity indicators. All the sludges, municipal or other, comply with the requirements of the legislation regarding the possibility of their application to agricultural soil (with the exception of SS2, due to its pathogenic microorganisms content), with a content of organic matter and nutrients that make them interesting to be applied to soil. The composts presented, in general, some constraints regarding their application to soil, and their impairment was due to the existence of heavy metal concentrations exceeding the proposed limit of the draft European legislation. As a consequence, with the exception of AWSSC, most compost samples were not able to meet these quality criteria, which are more conservative for compost than for sewage sludge. From the results, the composting of sewage sludge is recommended as a way to turn a less stabilized waste into a material that is no longer classified as a waste and, judging by the results of this work, with lower heavy metal content than the other composted materials, and without sanitation problems.